Development of E-Student Worksheet based on Guided Discovery of Membrane Transport Materials to Train Integrated Science Process Skills - Agustiningsih, Vidyasary; Dewi, Sari Kusuma (Journal of English Language and Education, 2026)
21st century education requires students to have integrated science process (KPST) skills. This research aims to develop E-LKPD based on guided discovery on membrane transport materials that are valid, practical, and effective in practicing KPST. This study uses a 4D development model (Define, Design, Develop, and Disseminate) and is tested on a limited basis in grade XI students. Data was collected through validation sheets, student response questionnaires, implementation observation sheets, and pre-test and post-test tests. The e-LKPD developed has five main features, namely Bio-Insight, Scilab Explore, Bio-Viz, Veri-Bio, and Bio-Conclusion to train KPST. The results of the study received a score of 97.12% and were included in the very valid category. Observation of activities received a score of 100% with a very practical category and the student response questionnaire obtained a score of 97.64% with a very practical category The learning outcomes of students with an N-gain score  of 0.80 included in the high category, and the achievement of KPST indicators with an average score of 37% in the pretest increased to 87% in the posttest, with  an N-gain score 0.80 which is included in the high category. Thus,  guided  discovery-based E-LKPD is declared valid, practical, and effective to train students' integrated science process skills.